Studies in the gas chromatography of ammonia, with special reference to packings containing solutions of silver salts in some organic solvents - Du Plessis, Louis Armand (Department of Chemistry, 2016)
It has been found that the gas chromatography of ammonia on certain fixed phases containing salts yields chromatograms consisting of a peak followed by a plateau or a succession of plateaux of progressively decreasing height. Such chromatograms have been interpreted in terms of ammine formation in the column and methods have been theoretically elaborated for using measurements on the chromatograms to find the dissociation pressures of the ammines and the ratios of ammonia taken up to silver in the fixed phase. These methods require the calibration of the detector, so that ammonia partial pressures can be found from chromatogram heights, and this has been done by a chromatographic method. In most cases, the ratio of ammonia to silver in the fixed phase does not yield conclusive information on ammnine composition, because there is usually evidence that the salt is present in different forms or is only partially converted to ammine.